Environmental density, safety, and restoration: a mixed-methods study of behavioral intentions in night-time tourism - Li, Sicheng; Wang, Jingqi (Frontiers in Psychology, 2026)
IntroductionDrawing on Stress Recovery Theory, this study examines how environmental density influences tourists’ behavioral intentions in night-time tourism contexts by integrating the Stimulus-Organism-Response model, Affective Events Theory, and Attention Restoration Theory.MethodsUsing a mixed-methods design, this study analyzes survey data from 653 tourists through Structural Equation Modeling and fuzzy-set Qualitative Comparative Analysis, complemented by field interviews.ResultsThe results show that environmental density directly weakens behavioral intention and indirectly affects it through a sequential pathway of perceived safety and emotional experience. Perceived restorativeness significantly buffers the negative effect of density on perceived safety. fsQCA reveals multiple equivalent configurations leading to high and low behavioral intention.DiscussionThe findings extend Stress Recovery Theory to night-time tourism contexts and highlight the importance of density management, safety enhancement, and restorative environmental design.